2022
DOI: 10.47700/jiefes.v3i1.4350
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Literasi Asuransi, Religiusitas, dan Kualitas Pelayanan terhadap Minat Generasi Milenial Menggunakan Asuransi Syariah

Abstract: Risk is something that cannot be predicted when it occurs and can cause a loss. Efforts to protect yourself become a necessary action to minimize the losses incurred. The millennial generation's concern for insurance is still lacking and tends to be more concerned with lifestyle than efforts to protect themselves by having insurance. This study aims to analyze the effect of insurance literacy, religiosity, and service quality on the millennial generation's interest in using sharia insurance. This study uses a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Consumers will certainly consider the quality of the services provided before using insurance. However, there is one study that supports the results of research conducted by Dan Intan Afryani which shows there is no influence of service factors with insurance ownership because customers look more at the price of insurance first when they want to enroll in an insurance program (Pramudya & Rahmi, 2022;Bahari & Basalamah, 2019;Rangkuti et al, 2022;Rouzaton, 2020).…”
Section: The Influence Of Service Factors On the Interest In Using Bp...mentioning
confidence: 83%
See 2 more Smart Citations
“…Consumers will certainly consider the quality of the services provided before using insurance. However, there is one study that supports the results of research conducted by Dan Intan Afryani which shows there is no influence of service factors with insurance ownership because customers look more at the price of insurance first when they want to enroll in an insurance program (Pramudya & Rahmi, 2022;Bahari & Basalamah, 2019;Rangkuti et al, 2022;Rouzaton, 2020).…”
Section: The Influence Of Service Factors On the Interest In Using Bp...mentioning
confidence: 83%
“…Plus the results of research conducted by, and which also found research results if the higher the level of public understanding related to insurance will certainly affect their interest in participating in insurance programs (Yoga, 2022;Ramadhan, 2023;TriSadewo, 2018;Pramudya & Rahmi, 2022).…”
Section: The Influence Of Information Factors On Interest In Using Bp...mentioning
confidence: 95%
See 1 more Smart Citation
“…keseluruhan mendapat manfaat dari peningkatan literasi asuransi; tujuan dari setiap perubahan polis terkait asuransi atau prakarsa pendidikan adalah untuk mempersiapkan penduduk dengan lebih baik untuk menghadapi dan mengelola risiko yang tak terelakan dan tak terduga yang mereka hadapi (Rahmi, 2022).…”
Section: Societyunclassified
“…Penyebaran pengetahuan tentang asuransi syariah merupakan langkah signifikan untuk memajukan perkembangan perbankan syariah di Indonesia. Menurut Survei Indeks Literasi Keuangan Sektor Perasuransian Tahun 2019 oleh Otoritas Jasa Keuangan (OJK), hanya 19,4% masyarakat Indonesia yang memiliki pengetahuan tentang perusahaan asuransi (Rahmi, 2022).…”
unclassified